Pangngaderreng as the Legal Epistemology of the Bugis Community: Integrating Sharia and Custom from the Perspective of Legal Pluralism - Nair, Rahmatun; Nuzul, A.; Keri , Ismail; Irfan, Ahmad; Kiramang, Khaeruddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This article analyzes pangngaderreng as a legal epistemology in the family law practice of the Bugis community by highlighting the integration between Islamic sharia normativity (sara’) and local rationality. This research uses empirical legal methods, analyzed with the theory of legal pluralism. Data were collected through in-depth interviews, observations and document studies. Interviews were conducted with religious leaders, academics, judges and community leaders as well as the community. While the documents analyzed were journal articles, books and a number of other scientific literature. The results of the study indicate that the elements of pangngaderreng have both epistemological and anthropological foundations. Pangngaderreng has four main elements, namely; ade’, rapang, wari’, and bicara, which function as legal reasoning mechanisms that ensure the application of sharia norms takes place contextually, deliberatively, and based on social propriety. Meanwhile, sara’ occupies a primary normative position that is functionally integrated in the local value structure. This article also emphasizes that the philosophical values ​​of Bugis culture remain intact, namely: accae (intelligence), lempu (honesty), warani (courage), and getteng (firmness), despite the challenges of social change. Theoretically, this article emphasizes the importance of a legal pluralism approach that recognizes all legal systems within Bugis society: Islamic law, customary law, and national law, which are integrated and intertwined in an accommodating and harmonious manner.